Magnetic resonance imaging findings of central nervous system in lysosomal storage diseases: A pictorial review. Issue 3 (25th December 2016) - Fagan, Nathan; Alexander, Allen; Irani, Neville; Saade, Charbel; Naffaa, Lena
Summary: Lysosomal storage diseases (LSD) are a complex group of genetic disorders that are a result of inborn errors of metabolism. These errors result in a variety of metabolic dysfunction and build‐up certain molecules within the tissues of the central nervous system (CNS). Although, they have discrete enzymatic deficiencies, symptomology and CNS imaging findings can overlap with each other, which can become challenging to radiologists. The purpose of this paper is to review the most common CNS imaging findings in LSD in order to familiarize the radiologist with their imaging findings and help narrow down the differential diagnosis.